Efficacy and Safety of Prolonged Treatment with Pemafibrate plus an HMG-CoA Reductase Inhibitor in Japanese Patients with Type 2 Diabetes Mellitus - Kusunoki, Masataka; Hisano, Fumiya; Matsuda, Shin-ichi; Kusunoki, Akiko; Tsutsumi, Kazuhiko; Miyata, Tetsuro (Drug Research, 2025)
It has been suggested that caution should be exercised when using HMG-CoA reductase inhibitor (statin) in combination with a drug of the fibrate family because of the potentially elevated risk of development of hepatic function impairment and myopathy. We conducted this present study to evaluate the efficacy and safety of treatment with a statin plus pemafibrate (a new fibrate) versus treatment with pemafibrate alone in Japanese patients with type 2 diabetes mellitus.In this study, a total of 23 Japanese patients with type 2 diabetes mellitus were divided into two groups: a group that received pemafibrate alone and a group that received pemafibrate+a statin for a period of 3 years, respectively. Blood levels of lipids and hepatic and renal function parameters were measured before and one and three years after the start of treatment.The pemafibrate-alone group showed reduction of the blood lipid levels, but no adverse changes of the hepatic or renal function parameters were observed. Similarly, the combined pemafibrate+statin treatment group also showed lowering of the blood lipid levels without any adverse changes of the parameters.Improvement of the blood lipid profile was observed in patients who received prolonged treatment with pemafibrate. Similarly, improvement of the blood lipid profile without any adverse changes of the hepatic or renal function parameters was also observed in patients who received prolonged combined pemafibrate+statin treatment. Thus, our findings confirm the safety and efficacy of pemafibrate administered either alone or in combination with a statin.
Keywords: pemafibrate; statin; combined treatment; type 2 diabetes mellitus